Lubricant‐Infused Anisotropic Porous Surface Design of Reduced Graphene Oxide Toward Electrically Driven Smart Control of Conductive Droplets' Motion. (10th April 2017) - Che, Pengda; Heng, Liping; Jiang, Lei
Abstract : The study of Nepenthes pitcher plants‐bioinspired anisotropic slippery liquid‐infused porous surfaces (SLIPS) is currently in its infancy. The factors that influence their anisotropic self‐cleaning and electric response of a drop's motion and the mechanism have not been fully elucidated. In order to address these problems, two new types of anisotropic slippery surfaces have been designed by using directional, porous, conductive reduced graphene oxide (rGO) films, and different lubricating fluids (conductive and nonconductive), which are used to study the influencing factors and the mechanism of anisotropic self‐cleaning and electric‐responsive control of a drop's motion. The results demonstrate the anisotropic self‐cleaning property of these two types of SLIPS is closely related to the interaction between liquid drops, lubricating fluids and dirt, and the conductive lubricating fluids filling the rGO porous film can reduce the response voltage of the electrically driven reversible control of a drop's slide. The uniqueness of this research lies in the use of two different lubricating fluids and graphene materials to prepare anisotropic SLIPS, identify the key factors to achieve an electrically driven system. These studies are essential for advancing the application of electronically responsive SLIPS in the fields of liquid directional transportation, microfluidics, microchips, and other related research. Abstract : Two types of anisotropic slippery surfaces are prepared using directional, porous, conductive reduced graphene oxide films, and different lubricating fluids (conductive and nonconductive). The electrically driven reversible control of a drop's sliding motion can be achieved on a conductive‐lubricant‐filled porous film under a small applied voltage.